Correction: A comparative analysis of the efficiency, timing, and permanence of CO2 removal pathways. Issue 1 (20th December 2022) - Chiquier, Solene; Patrizio, Piera; Bui, Mai; Sunny, Nixon; Mac Dowell, Niall
Abstract : Correction for 'A comparative analysis of the efficiency, timing, and permanence of CO2 removal pathways' by Solene Chiquier et al., Energy Environ. Sci., 2022, 15, 4389–4403, ; https://doi.org/10.1039/D2EE01021F .